IMPACT OF HIGH FREQUENCY ELECTROMAGNETIC FIELD ON SURVIVAL RATE AND THE MORPHOLOGY OF PATHOGENIC BACTERIA - S. H. Salmen1and S. A. Alharbi (Journal of Animal and Plant Sciences, 2017)
This study aimed to evaluate of impact of exposure to high frequency-electromagnetic fields on the survival rate and the morphology of bacteria. Three bacterial strains namely Staphylococcus aureus (ATCC 29213), Staphylococcus epidermidis (ATCC 25923), and Pseudomonas aeruginosa (ATCC 27853) were exposed to HF-EMF irradiation at 900MHz and 1800 MHz for 2 hour. After exposure, the viable counts (CFU/ml) of exposed bacteria were enumerated. The results showed that exposure to radiations at 900 MHZ and 1800 MHz led to reduction in viable counts compared to controls which were not subjected to exposure to irradiation. Further the impact of irradiation on cell morphology was evaluated by scanning electron microscopy (SEM). Results obtained for the SEM studies clearly showed that the HF-EMF irradiation resulted in changes in cell shape and size when compared to those cells which were not exposed (control). Cell diameters were observed to be reduced compared to that of unexposed cell. The SEM results also indicated shrinkage of bacterial cells resulting in changes in cell shape. It is concluded that HF-EMF irradiations emitted by mobile phones affect the survival of viable bacteria in the environment.
Keywords: High frequency electromagnetic field; Bacteria; Survival rate and Morphology